Monetary Transmission Mechanism, Oil Price Shocks and Economic Growth of Nigeria: Array - Fadiran, Taiwo Phebe (Acta Universitatis Danubius. Œconomica, 2020)
The paper investigates the relationship between monetary transmission mechanism, oil price shock and Nigeria economic growth from 1980 to 2018. Data were collected on major variables such as oil price, balance of payment, interest rate, exchange rate, inflation rate and GDP growth rate. Structural Vector Auto-Regression SVAR technique was applied and the results show that oil price shocks affect the channels in the MTM differently. While some channels in the MTM are significantly responsive to oil price shocks, some are not. The effect of oil price shocks on domestic price level in the economy is not direct. The exchange rate shocks have the highest influence on the domestic price level in Nigeria despite the fact that inflation rate does not respond significantly to oil price shocks but it does to exchange rate shocks and the economy responds significantly to inflation shocks. This sequence of reactions underscores the importance of both exchange rate and price channels in transmitting the shocks from oil price to the domestic economy.